Analysis of Work Readiness Personality Attributes Students of Class XI SMK Negeri 8 Bandar Lampung School Year 2022/2023 After Covid-19 Pandemic - Zahra Rachma Putri; Muhammad Nurwahidin; Shinta Mayasari (CV. Rayyan Dwi Bharata, 2023)
The role of guidance and counseling at school is one component of education aimed at helping facilitate learners (students) to achieve optimal self-development. Providing facilities for the development of students' abilities and self-establishment is one of the duties of Guidance and Counseling teachers at school. In a vocational high school that prepares students to become work-ready graduates, counseling teachers take part in shaping the work-ready character of these students, by providing guidance and counseling services to students according to their needs, but as we all know, new student learning takes place offline again after the last two years of running online due to the covid-19 virus outbreak which requires online learning from home making it less optimal to provide guidance and counseling services. The method used in this research is quantitative method. The population in this study amounted to 513 respondents with a sample of 128 respondents, this research was conducted at SMK 8 Bandar Lampung, data collection techniques using a work readiness questionnaire and analysis of work readiness personality attributes. There were 128 students in class XI of SMK Negeri 08 Bandar Lampung, 70 students (54.6%) had high work readiness, 56 students (43.7%) had moderate work readiness, and 2 students (1.5%) had low work readiness.... Students already have self-mastery of the attitudes and behaviors that a person must have to be declared ready to work. In this study, the form of work readiness is reviewed from personality attributes, namely work ethics, responsibility, enthusiasm for effort, time management, critical thinking skills, communication, and cooperation. Students who are in the high category can be declared to have been able to adjust to their work environment or to be ready to work.